Development of a rapid diagnostic technique for equine influenza - D. Abdul Hadi, Abdul Rahman (2012)
Equine influenza virus (EIV) is a highly contagious and widely distributed respiratory disease of equiadae caused by a type A influenza virus from the family Orthomyxovirus. Influenza in equines is caused by two types of viruses, H3N8 and H7N7. The viruses currently circulating among horses are of the H3N8 sub-type. H7N7 has not been reported for more than three decades from any part of the world. Vaccination against equine influenza, a powerful tool for the control of the disease, may result in issues related to vaccinations interferes with sero-surveillances program of EIV infection.The use of vaccination against equine influenza have greatly worldwide acceptance if a reliable test were available that clearly discriminate between naturally infected and vaccinated animals (DIVA). Because horses that were vaccinated with ‚inactivated vaccines‛ have not produced non-structural protein (NS1) specific antibodies, while they have presented in the naturally infected horses, therefore, NS1 protein considered as an attractive candidate for a DIVA differential diagnosis test. The objectives of the present study were to detect, identify and develop a diagnostic kit for EIV. For virus detection, identification and isolation, a total of 162 nasopharyngeal swabs were collected during 2009-2010. Our study showed that the prevalence of viral nucleic acid was detected in 50 out of 162 (31%) nasopharyngeal swabs. All positive samples were subjected for virus isolation in 9-11 days embryonated specific-free-pathogen eggs (SPF) followed by hemagglutination test, and RT-PCR. Embryonic death did not occur during the five passages and all embryos remained alive. However, the results from HA test and RT-PCR were also showed negative results. The failure to isolate the circulating viral antigen was possibly due to horses that were not in the acute phase of the disease during the period when samples were collected, thus they did not shed a live virus, and the samples were collected from a situation of no form of outbreaks.With respect to development, of a rapid and reliable diagnostic technique, the NS1 gene of H3N8 subtype was amplified by RT-PCR and expressed in prokaryotic expression plasmid pRSET B in E. coli strain BL21 (DE3)plysS after induction with IPTG. The 6x His-tagged recombinant fusion proteins were purified using the Pro BondTMPurification system and the expressed protein was identified by SDS-PAGE and western-blotting. A recombinant protein of approximately 13kDa was produced. The results showed that the recombinant NS1 protein was expressed and the optimal coating concentration was 2.01μg/ml, the optimal serum dilution was 1:100, and the optimal HRP-IgG dilution was 1:10000. For evaluation and validation of the developed NS1-ELISA, a total of 344 serum samples were collected from two groups of horses, 144 samples from vaccinated and 200 samples from unvaccinated groups. The results of the newly developed NS1-ELISA were compared to Haemagglutination inhibition (HI) test, indirect equine influenza IgG-ELISA (IBL, Germany) and competitive influenza A IgG-ELISA (IDEXX-USA). The results shows the potential superiority of the NS1-ELISA in the differentiation of vaccinated from unvaccinated (infected animals).In conclusion, these results demonstrate the potential benefit of a simple, specific ELISA for anti-NS1 antibodies that may have diagnostic value for the equine industries in Malaysia, and also useful method for serological diagnosis to differentiate vaccinated from naturally infected horses. This recombinant NS1-based ELISA could therefore be a good alternative to currently available kits for detection of antibody to EIV.